The anatomy of a Mesopotamian city - Stone, Elizabeth Caecilia,Zimansky, Paul E.,Steinkeller, Piotr,Stone, Elizabeth C. (Eisenbrauns, 2004)
Research design – The site and its environs – A history of Mashkan-shapir and its role in the Kingdom of Larsa / Piotr Steinkeller – Survey methods and analytic procedures – Types and characteristics of surface features – The objects – A building inscription of Sin-iddinam and other inscribed materials from Abu Duwari / Piotr Steinkeller – Locational data – Distribution of features and objects in the urban environment
9781575060828
Keywords: Excavations (Archaeology); Excavations Archaeology